Correction: Gtsf1 is essential for proper female sex determination and transposon silencing in the silkworm, Bombyx mori. - Kai Chen; Ye Yu; Dehong Yang; Xu Yang; Linmeng Tang; Yujia Liu; Xingyu Luo; James R Walters; Zulian Liu; Jun Xu; Yongping Huang (PLoS Genetics)
[This corrects the article DOI: 10.1371/journal.pgen.1009194.].